The adoption of good practices of handling improves dairy calves welfare: Case studysh - Silva-Antunes, Livia Carolina Magalhães; Costa, Mateus José Rodrigues Paranhos da (Acta Scientiarum. Animal Sciences, 2021)
The aim of this study was to assess the effect of the adoption of a set of good practices of handling on dairy calves welfare. Data were retrieved from the records of a commercial farm, considering three periods: Conventional handling (CH, 12 mo.), transitional period (TP, 4 mo.), and good practices handling (GPH, 12 mo.). During CH calves were kept in individual pens, milk-fed in open pails and subjected to abrupt weaning; while during TP and GPH they were kept in groups, milk-fed in nipple-pails, brushed for 5 min. once a day, and subjected to progressive weaning. TP was assumed as a training period necessary for GPH implementation. The percentages of calves treated with antibiotics and numbers of deaths per month were used as indicators of calves welfare. Statistical analysis was performed using a logistic regression model to compare the number of deaths per month between CH and the other periods. Chi-square test was used to compare the percentage of animals treated with antibiotics per month. Results showed that CH had a higher risk of calf’s death then TP and GPH, as well as a higher percentage of animals treated with antibiotics. In conclusion, the adoption of good practices of handling improved dairy calves welfare.